Efficacy of lenalidomide, bortezomib, and prednisolone in patients with relapsed or refractory multiple myeloma - T. A. Мitinа; A. K. Golenkov; E. V. Trifonova; E. V. Kataeva; L. L. Vysotskaya; Yu. B. Chernykh; S. G. Zakharov; K. A. Belousov; A. V. Karaulov (Онкогематология, 2015)
49 patients aged 28 to 81 years old (median age of 55 years old) with relapsed or refractory multiple myeloma (MM) were enrolled in the study. The relapse was diagnosed in 25 (51 %) patients, the refractory disease was determined in 24 (49 %) patients (including primary refractory disease in 14 (28.6 %) patients). The prior therapy for all patients included bortezomib-based treatment in combination with thalidomide and autologus stem cell transplantation (8.1 %). Lenalidomide had not been used in the previous therapeutic regimens. All patients were given the original treatment regimen, which included lenalidomide, bortezomib, and prednisolone (RVP). The therapy was made up of seven induction cycles with each one lasting for 48 days. Length of courses was 14 days. After seven cycles of RVP therapy were over, such results were achieved: complete response (CR) in 1 (2 %) patient; very good partial response (VGPR) in 4 (8 %) patients; partial response (PR) in 26 (53 %) patients; minimal response (MR) in 2 (4 %) patients; stable disease (SD) in 8 (16.3 %) patients, and progressive disease (PD) in 8 (16.3 %) patients. The objective response rate, including CR+VGPR+PR, was obtained in 31 (63.1 %) patients. The objective response rate, including MR, was seen in 33 (67.1 %) patients. Hematological and non-hematological toxicities were moderate. Taking into account the above, the RVP therapeutic regimen has demonstrated its efficacy as a second-line therapy for MM, and its clinical use can solve the problem of relapsed/refractory to bortezomib-based regimens MM management.